Imageability Asymmetry in Mental Lexicon of Croatian Aphasic and Healthy Speakers - Peti-Stantić, Anita (Array, 2014)
Imageability has been argued to induce asymmetry in processing of nominal lexical units as this feature of the mental lexicon unit is sensitive to the stimulus modality and to the conceptual system. Double modality of the representation of concrete nouns in the mental lexicon, verbal and non-verbal representation, contrasted with single, verbal, representation in abstract nouns [Paivio] is argued to facilitate the processing of a concrete noun and slow down successful retrieval, access and any further processing of an abstract noun [Sabsevitz et al.]. However, research confirming double dissociation of imageability underlines the claim that for the account of imageability it is equally crucial to verify the processing capacity of the mental lexicon’s interface with the conceptual system [Gvion & Friedmann]. The first aim of the study is to investigate whether is a significant difference in the semantic processing of high and low imageable words in people with aphasia compared to the healthy control speakers when presented with a visual or auditive stimulus. The second aim of the study is to investigate whether the greater asymmetry in semantic processing of high and low imageable words stems from the incoming stimulus modality that is impaired in aphasic people, or to the interface processing capacity of the mental lexicon with the conceptual system. Research was conducted based on the three tests designed to examine the processing of the lexical feature of imageability: Auditory Synonym Judgements, Written Synonym Judgements and Word Semantic Association from the battery of tests PALPA adapted for Croatian [Kay et al., Erdeljac et al.]. To reduce the effect of perceptive impairments, general semantic processing was verified by conducting two follow-up PALPA comprehension tests: Spoken Word-Picture Matching and Written Word-Picture Matching. The study included 30 participants with different type of aphasia (motor, sensory, and global) and 30 paired healthy participants ; all native speakers of Croatian. In line with the predictions, there was a statistically significant difference between experimental and control group ; the experimental group further confirmed the predictions by achieving significantly lower results with respect to low- imageable words. Difficulties in recognition of low imageable words in aphasics confirm the existing variations in the organization of processing pathways as imagined by Modular Models depicted in PALPA. These variations also correlate with the interaction of stimulus modality and facilitating effects due to representation modality as predicted by Dual-Coding Theory. Double-dissociation with respect to mental lexicon’s interface to conceptual system is further discussed based on the results of the two comprehension tests. Selected references: Gvion, A. & N. Friedmann (2013) A selective deficit in imageable concepts: a window to the organization of the conceptual system ; Frontiers in human neuroscience ; 7 ; 1-13. Kay, J. et al. (1992). Psycholinguistic Assessment of Language Processing in Aphasia (PALPA). London: Lawrence Erlbaum Associates. Paivio, Allan (2010) Dual coding theory and the mental lexicon ; The Mental Lexicon ; 5 (2) ; 205–230. Sabsevitz, D. S. et al. (2005) Modulation of semantic system by word imageability ; NeuroImage ; 27 ; 188–200. Erdeljac et al. (submitted) Lexical Feature of Imageability in the Mental Lexicon of People with Aphasia. Govor/Speech.